LANDSCAPE FRAGMENTATION AND FIRE VULNERABILITY IN PRIMARY FOREST ADJACENT TO RECENT LAND CLEARINGS IN THE AMAZON ARC OF DEFORESTATION - Alvarado, Ernesto; Sandberg, David V.; de Carvalho Jr., Joao Andrade; Gielow, Ralf; Santos, José Carlos (Floresta, 2004)
Deforestación extensiva en el Amazonas ha creado una selva bastante fragmentada en regiones con tasas altas de deforestación y de uso del fuego para limpia y mantenimiento de terrenos. El bosque en la interfase con estas deforestaciones sufre cambios drásticos en microclima, vegetación y procesos ecológicos, los cuales son favorables para la combustión bajo las copas después de una sequía prolongada. Un incremento en el uso del fuego, aunado a una mayor área de bosque vulnerable a incendios es una amenaza para la integridad y sustentabilidad de selvas tropicales. Se presentan resultados de estudios conducidos en Mato Groso de 1997 al 2003 como parte de experimentos para estudiar combustión de biomasa, tasas de liberación de carbono y flamabilidad de selvas. Se monitorearon cambios en susceptibilidad a incendios en la interfase entre el bosque y áreas recientemente deforestadas durante la temporada de sequía, al final de la cual se desarrollaron quemas experimentales. Abstract Extensive deforestation in the Amazon has created a highly fragmented forest in regions with an extensive rate of land use conversion and use of fire for land clearing, agriculture and grassland maintenance. The forest on the interface with land clearings suffers drastic changes in micro weather, vegetation, and ecological processes. Those altered conditions are favorable to sustaining understory fires after a prolonged drought. An increasing amount of fire usage, coupled with large areas of forest vulnerable to fire creates a new threat to the integrity and sustainability of the tropical forests in Amazonia and elsewhere in the tropical world. This paper presents the results of experimental burnings conducted from 1997 to 2003 in Mato Grosso. The study monitored the change in vulnerability of the interface between primary forest and recent deforested patches, monitored fire behavior and depth of fire penetration in the undisturbed forest on the edge of land clearing.